MORPHOSYNTACTIC FEATURES OF ADVERBIAL CLAUSES IN ROMANCE LANGUAGES -CONSEQUENCES OF LANGUAGE CONTACT OR LATIN INHERITANCE?- - Bodoc, Alice-Magdalena (PEOPLE: International Journal of Social Sciences, 2019)
The starting point of the present paper is a simple question: To what extent do linguistic facts encountered in Romanian exist in other Romance varieties? In order to answer this question, I put forward a cross-linguistic study of the Romance languages that aims at an interdisciplinary effort, a perspective that is going to add new and useful information to the literature, especially at the international level, that lacks, in many cases, examples from Romanian. On the basis of an original media discourse corpus, collected from three Romance varieties (Romanian, Italian and French), I advance a comparative perspective, focused on the connectors of the complex sentences. Since the aim of this paper is neither to defend/to contradict some linguistic theory of the syntactic variation, nor to develop a new grammatical theory, the focus will be on the description of the identified linguistic data, and on the motivation of their existence/absence in the three related languages.